Performance of water hyacinth (eichhornia crassipes) in palm oil mill effluent (POME) treatment - Siti Nur Aqilah, Majid (2019)
Wastewaters from industrial places are very complex and lead to water pollution if discharge untreated, especially due to its high organic loading. Palm oil mill effluent (POME) is a brownish liquid that contains high amount of biochemical oxygen demand (BOD), chemical oxygen demand (COD) and other parameters have been produced from the palm oil processing plants. Therefore, wastewater treatment such as phytoremediation is needed to decrease the effect of contamination. Phytoremediation is a process using aquatic plants for pollution and waste management. The objectives of this research were to investigate the characteristics of Palm Oil Mill Effluent (POME) for baseline information and to reduce the waste contaminants using Eichhornia Crassipes before discharging to the environment. Parameter concerns were biochemical oxygen demand, chemical oxygen demand, ammonia-nitrogen (NH3-N), total suspended solids (TSS), turbidity, pH, dissolved oxygen (DO), cadmium (Cd), lead (Pb) and copper (Cu). This experiment was conducted with three different concentrations of sample which were 30%, 20% and 10% concentration. The aquatic plant was preserved in distilled water for a week before putting them into each of the concentrations. This experiment was conducted for three weeks after putting the plant into each concentration and the result of all parameters were taken and measured once a week for each concentration. After week 3, 72.31%, 73.23% and 82.85% of COD had been removed from 30%, 20% and 10% of sample concentration, while 70.18%, 75.16% and 80.88% for BOD had been removed from 30%, 20% and 10% of sample concentration. Then, the removal for NH3-N were 69.60%, 72.38% and 77.01% from 30%, 20% and 10% of sample concentration, whereas for TSS removal were 68.39%, 73.53% and 78.91% from 30%, 20% and 10% of sample concentration. The percentage of turbidity removal efficiency were 65.63%, 68.18% and 72.73% from 30%, 20% and 10% of sample concentration. For heavy metal, the Cd removal from 30%, 20% and 10% of sample concentration were 76.02%, 80% and 87.56% respectively, while the Cu removal from 30%, 20% and 10% of sample concentration were 67.55%, 69.18% and 72.11% respectively. Next, the Pb removal were 75.58%, 77.94% and 79.63% from 30%, 20% and 10% of sample concentration respectively. But the value for pH and DO were negative value which means the values were increased week by week. After week 3, the pH increasing efficiency was 23.73%, 24.59% and 25.40% from 30%, 20% and 10% of sample concentration while 64.00%, 65.00% and 85.71% of DO had been increased from 30%, 20% and 10% of sample concentration respectively. As a conclusion, phytoremediation process can be used as an industrial waste treatment and Eichhornia Crassipes also give high efficiency in removing contaminant in 10% concentration of palm oil mill effluent.